PENGARUH KUALITAS AUDIT DAN TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA - Fadlila Hidayati; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
The aim of this study is to examine the effect of audit quality on earning management in companies listed on the Indonesia Stock Exchange. Audit quality in this study is measured by audit fee and audit firm size while corporate governance is measured using the audit committee meetings and board independence and size. Earnings management in this study is measured by discretionary accruals of the company. Firm size, leverage, cash flow from operations, and firm growth used as control variables.The population of this study are non-financial companies listed in Indonesia Stock Exchange (BEI) year period 2017-2020. The sample of this study was obtained using purposive sampling method with a total sample of 412 companies. The analytical technique used to test the hypothesis in this study is multiple regression analysis with the help of SPSS software. The result of this study shows that audit fee, audit firm size have a negative and significant effect on earning management. The corporate governance variables, board independence and audit committee meeting, showed significant negative results, while board size had no significant effect on earnings management.